(untitled) (IPS Journal of Nutrition and Food Science, 2023)
In the emerging global food scenario, sorghum is a healthy cereal crop used by human beings and has been recognized to have considerable potential to be used in a variety of food products. Germination is a natural processing technique used for the biological activation of grains to improve their nutritional and functional properties. In order to improve the germination of grains, different techniques have been established; therefore, the current study was conducted to analyze the effect of ultrasound and microwave techniques on sorghum grain germination parameters. Overnight steeped sorghum grains were divided into four groups. The first group was not subjected to any treatment. The second group was subjected to ultrasonic treatment, the third group was exposed to microwave treatment, and the fourth group was treated with combined MW & US applications for different intervals. Germinated grains were measured for the shoot length and root length, total weight, germination %, seedling vigor index, and the ratio of root length versus shoot length. It was found that ultrasound-processed treatment US1 (40% amplitude for 5 min) and microwave-processed treatment MW2 (700 W for 5 sec) significantly improved the germination parameters. Pre-sowing physical techniques cause disturbance of the seed coat, which enabled water diffusion into the seeds inducing a higher rate of enzymatic reactions, and the start of the initial development stages consequently resulted in faster and more effective germination.